2019
DOI: 10.4103/ijpsym.ijpsym_343_18
|View full text |Cite
|
Sign up to set email alerts
|

Gender Variability of Perceived Stress and Negative Inferential Feedback in Depression

Abstract: Background: The role of negative inferential feedback and perceived stress in hopelessness depression is known. However, studies on their gender variability are lacking. The difference in various domains of negative inferential feedback and its impact on cognitive hopelessness, depression, and outcome of psychotherapy between men and women has been hypothesized. Aims: This study analyzed the difference in stress levels and hopelessness in the form of negative inferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…What has changed is the way that each group deals with the new situation caused by COVID-19, highlighting the importance of the coping strategy as a quick response damper to keep the new routine without major losses. Studies have documented differences between women and men with respect to symptom reporting, treatment seeking, coping strategies and several neurobiological variables pertinent to depression (Nayak et al, 2019;Wellman et al, 2018). It has been shown that women are twice as likely as men to develop depression and suffer stress, in addition to presenting less resilience (Nayak et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What has changed is the way that each group deals with the new situation caused by COVID-19, highlighting the importance of the coping strategy as a quick response damper to keep the new routine without major losses. Studies have documented differences between women and men with respect to symptom reporting, treatment seeking, coping strategies and several neurobiological variables pertinent to depression (Nayak et al, 2019;Wellman et al, 2018). It has been shown that women are twice as likely as men to develop depression and suffer stress, in addition to presenting less resilience (Nayak et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented differences between women and men with respect to symptom reporting, treatment seeking, coping strategies and several neurobiological variables pertinent to depression (Nayak et al, 2019; Wellman et al, 2018). It has been shown that women are twice as likely as men to develop depression and suffer stress, in addition to presenting less resilience (Nayak et al, 2019). The Unicamp community follows this same pattern described in the literature, with high scores for perceived stress, depressive signs and low score for resilience when compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Parker et al [ 28 ] reported significant improvements in fatigue, self-efficacy, pain and health through effective stress management. It has been reported that women are also more likely to experience stress from major life events and play more vulnerable social roles than men, slowing the development of stress management and increasing the incidence of depression [ 29 , 30 ]. Therefore, even if there was clinical improvement in the treatment of illness, subjective factors such as the patient’s perception of difficulty in daily life, confidence in coping with stress, level of contentedness in stress and expected health condition were considered to be related to depression.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to higher self-awareness about the disease impact and heightened spread [14]. Specialists who are more likely to handle stress than others may suffer from higher stress due to any negative life event, self-perception or coping style [15].…”
Section: Discussionmentioning
confidence: 99%